Echocardiographic diagnosis of aortopulmonary window in a 4-day-old baby - (:unkn) unknown (My University, 1999)
Aortopulmonary window is a rare cardiac abnormality leading to pulmonary vascular disease unless diagnosed in early infancy. Echocardiographic diagnosis may be difficult if it is not searched for. Aortopulmonary window must be considered in the differential diagnosis of patent ductus arteriosus and truncus arteriosus because of their similar clinical findings and natural course. Early diagnosis is essential for prevention of complications, especially the Eisenmenger syndrome. We herein present an aortopulmonary window type I case diagnosed by echocardiography and treated surgically in a-four day-old baby.
Keywords: Aortopulmonary window; Congenital heart disease; Echocardiography